2018
DOI: 10.12707/riv17103
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perception of the sleep habits and quality of preschool-aged children

Abstract: Perceção parental sobre hábitos e qualidade do sono das crianças em idade pré-escolar Percepción parental sobre los hábitos y la calidad del sueño de los niños en edad preescolar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Childhood and adolescence are important periods of life for the development of healthy lifestyle habits and important physiological processes that can be carried into adult life [ 1 ]. Among these physiological processes is sleep quality, as it is at this stage that major changes occur in the neuromotor and hormonal systems, in which physical rest during sleep is extremely important for child growth and development, as well as changes and physical maturation in adolescents [ 2 ]. Therefore, sleep is characterized by a physiological need that influences biological functions, such as organic restoration, energy conservation, and physical and mental balance and when there is an absence or sleep disorders, neurodegenerative diseases develop, interfering in the individual's quality of life [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood and adolescence are important periods of life for the development of healthy lifestyle habits and important physiological processes that can be carried into adult life [ 1 ]. Among these physiological processes is sleep quality, as it is at this stage that major changes occur in the neuromotor and hormonal systems, in which physical rest during sleep is extremely important for child growth and development, as well as changes and physical maturation in adolescents [ 2 ]. Therefore, sleep is characterized by a physiological need that influences biological functions, such as organic restoration, energy conservation, and physical and mental balance and when there is an absence or sleep disorders, neurodegenerative diseases develop, interfering in the individual's quality of life [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actigraphy results showed that they spent less time in bed. During the preschool years, sleep patterns were more organized, stable, and less disrupted, due to maturational reasons ( 33 , 43 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep and rest are essential for children's wellbeing, as physical rest and energy recovery have an important impact on their growth and development, and are fundamental aspects for restoring health (18) . In the hospital environment, family caregivers seek to meet children's biological needs and are responsible for their care.…”
Section: Discussionmentioning
confidence: 99%